Defensive plasticity in South American rattlesnakes Crotalus durissus - Alves-Nunes, João Miguel [UNESP]; Fellone, Adriano; Ricaurte, Juan Camillo Diaz (British Herpetological Society, 2024)
Reptiles exhibit defensive responses in diverse ways, influenced by situational factors. Snakes, such as the South American rattlesnake Crotalus durissus, display complex defensive responses, adapting tactics based on circumstances when encountering potential predators. Environmental and intrinsic parameters shape snake behaviour during predator encounters. This study employs distinct stimuli to investigate behavioural changes and whether snakes adapt defensive strategies. We compare the behaviours of rattlesnakes before and after an aversive stimulus involving physical contact. Following encounters with higher-risk stimuli, snakes become more defensive. Findings reveal that snakes alter strategies based on threat intensity. This phenomenon might be influenced by the potential cost of defense and prior interactions with predators. The study underscores the intricate nature of snake defensive behaviour.
Keywords: active behaviours; antipredator behaviour; aversive stimulus; behavioural cost; behavioural plasticity